Preparation method and application of high internal phase emulsion porous foam material with hydrophilicity gradient in thickness direction
By performing different hydrophilic treatments on the two surfaces of the high internal phase emulsion porous foam material, the hydrophilic gradient in the thickness direction is achieved, the contradiction between the surface dryness and absorption speed after the liquid is absorbed is solved, and the disposable sanitary products are satisfied. Liquid absorption and storage requirements.
Patent Information
- Application Number
- CN202410376857.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The existing high internal phase emulsion porous foam materials have reduced hydrophilicity after multiple absorption of liquids, resulting in the risk of liquid leakage. Improving hydrophilicity will affect the surface dryness and skin contact comfort, making it difficult to simultaneously in disposable sanitary products. Meets the requirements of liquid absorption speed and surface dryness.
Using a high internal phase emulsion porous foam material preparation method with hydrophilic gradient in the thickness direction, the first surface has a lower hydrophilicity and diffusivity by implementing different hydrophilic treatment agents on the two surfaces. The second surface has a higher hydrophilicity, thereby storing and diffusion on the second surface after rapidly absorbing the liquid on the first surface.
It achieves low material thickness, simple and efficient process, and meets the requirements of liquid storage and diffusion mainly on the second surface while the first surface remains relatively dry, improving the absorption efficiency and use comfort of the material.
Smart Images

Figure CN118374052B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophilic porous absorbent materials, and more specifically to a preparation method and application of a high internal phase emulsion porous foam material having a hydrophilicity gradient in a thickness direction. Background Art
[0002] High internal phase emulsion (HIPE) is an ultra-concentrated emulsion system with an internal phase (dispersed phase) volume fraction exceeding 74%. At a higher dispersed phase volume fraction, the liquid of the dispersed phase is deformed into a polyhedron, and the continuous phase becomes a thin-walled grid structure. In the high internal phase emulsion of the W / O system, when the dispersed phase is an aqueous phase and the continuous phase is a polymerizable monomer, the polymerization reaction of the continuous phase will form a porous material with a large number of internal cavities. The open-cell foam made from the high internal phase emulsion is particularly suitable as an absorbent material in disposable sanitary products such as diapers and sanitary napkins, or for body fluid absorption and wound healing in wound care products. In disposable sanitary products, the porous material prepared from the high internal phase emulsion has the advantages of lighter weight, higher softness, thinner thickness, and no discomfort caused by the granularity of SAP, compared with traditional absorbent materials such as fluff pulp or super absorbent resin (SAP).
[0003] Generally, HIPE foam is a porous material of polyacrylate, and the hydrophilicity of the material itself is poor. In disposable sanitary products, in order to ensure good absorption of aqueous liquids such as urine and body fluids by high internal phase emulsion foam, the HIPE foam is usually required to be hydrophilized to make the material hydrophilic. Chinese patent CN1070924A discloses a method for converting a polymer foam plastic that is actually hydrophobic into a foaming material suitable for absorbing hydrophilic liquids, the method comprising mixing certain types of surfactants and a solution formed by a solvent such as water and certain types of hydrophilic salts into the polymer foam material, and then drying the polymer foam material treated in this way to remove the solvent, thereby leaving the surfactant and hydrophilic reagent salt with a certain hydrophilic amount that are substantially evenly distributed and mixed in the foam material; however, the problem of treating the hydrophobic porous material with a water-soluble surfactant to make it hydrophilic is that after the porous material absorbs liquids for many times, the hydrophilic surfactant and hydrophilic salts attached to the inner wall of the porous material will dissolve into the liquid from the surface of the porous material, resulting in a gradual decrease in the hydrophilicity of the porous material. When the porous material is used in disposable sanitary products, after the porous material treated with the hydrophilic surfactant and the hydrophilic salt absorbs liquids for many times, the hydrophilicity will decrease because the hydrophilic surfactant and the hydrophilic salt are lost with the liquid, bringing the risk of liquid leakage. In order to solve the above-mentioned problem of decreased hydrophilicity, the current method of hydrophilic treatment is usually to treat the prepared HIPE porous foam material with an aqueous solution of a surfactant with a relatively high HLB by immersing, spraying, applying, etc., so that the hydrophilic surfactant adheres to the pore wall of the HIPE porous foam material.
[0004] Research has found that as the hydrophilicity of HIPE porous foam materials increases, the HIPE porous foam materials absorb blood faster; however, while increasing the absorption rate of blood by porous foam materials, it also brings some problems. One of the main problems is that while the hydrophilicity of porous foam materials increases, the infiltration of blood under the action of gravity also increases, which increases the retention of blood on the surface of porous foam materials and on the pore walls close to the surface, resulting in a decrease in surface dryness and skin contact comfort. At the same time, the hydrophilicity of the surface of the porous foam materials treated with hydrophilicity is increased, and the lateral diffusion of liquid on the surface is increased, resulting in a larger wet surface area, which leads to a further decrease in surface dryness and skin contact comfort. Therefore, the hydrophilicity of HIPE porous foam materials has a dual impact on the application performance of HIPE porous materials in disposable sanitary products. Generally speaking, the increase in hydrophilicity increases the absorption rate of body fluids by porous materials, while increasing the retention of liquid on the surface of sheet-like porous materials, resulting in a decrease in surface dryness. Low hydrophilicity will reduce the absorption rate of body fluids by porous materials, but for a period of time after absorption, the surface dryness of sheet-like porous materials will be better.
[0005] The pore size of HIPE porous foam materials can be adjusted by adjusting the formula of water phase and oil phase, adjusting the type and amount of emulsifier, changing the shear rate during emulsification and changing the emulsification temperature. In addition to differences in softness and toughness, porous foam materials with different pore sizes also have different liquid absorption speeds, liquid absorption amounts and lateral diffusion areas of liquid after absorbing liquid. Hydrophilic porous foam materials with larger pore sizes are more conducive to the rapid absorption of viscous body fluids such as blood, but are not conducive to the diffusion of liquids, and larger pore sizes will actually cause the porous materials to reduce the absorption rate of body fluids. Hydrophilic porous materials with small pore sizes have higher absorption rates for body fluids and better diffusion. Generally speaking, within a certain range, the more emulsifiers are added, the easier it is to emulsify, the smaller the volume and the greater the number of droplets in the emulsion internal phase, and the porous materials with smaller pore sizes can be obtained after the emulsion is solidified. The faster the shear rate during the emulsification process, the smaller the volume of the emulsion internal phase within a certain range, and the smaller the pore size of the high internal phase emulsion porous material obtained. Another factor that has a significant impact on pore size is the ratio of water phase to oil phase. The water phase is the internal phase. The higher the volume ratio of the water phase to the oil phase, the larger the pore size of the high internal phase emulsion porous material. In addition, it is very important to note that the type of polymerized monomers of the oil phase and the corresponding emulsifier combination are important factors affecting the pore size of the high internal phase emulsion porous material. Therefore, the pore size has a two-way effect on the hydrophilic high internal phase emulsion porous material. Generally speaking, the larger the pore size, the faster the absorption rate of viscous body fluids, but the absorption rate and diffusion are lower. The smaller the pore size, the slower the absorption rate, but the absorption rate and diffusion of viscous liquids will be better.
[0006] In view of the influence of the hydrophilicity of the above porous materials and the pore size on the absorption speed, diffusion, and surface dryness of the porous materials, a better choice is to prepare multilayer materials with different pore sizes, for example, the upper layer material has a larger pore size and a fast absorption speed, which can allow the fluid to quickly enter the lower layer, and the lower layer material has a stronger liquid storage capacity than the upper layer material, which can store the liquid from the upper layer material to ensure the dryness of the upper layer material. The Chinese patent with publication number CN1228016A discloses a method for preparing a porous material with multiple layers of different functions, wherein the upper layer porous material has a larger pore size and a smaller capillary specific surface area, and the lower layer material has a relatively smaller pore size and a larger capillary specific surface area. The Chinese patent with publication number CN103917210A discloses a double-layer absorbent core structure, the functions of the upper and lower layers are similar to those of the upper and lower layer materials mentioned above. Chinese patents CN105451702A, CN106456412A, and CN106943238B disclose a double-layer absorbent core structure. Chinese patent with publication number CN106470711A discloses a double-layer open-cell foam structure, wherein the two layers of open-cell foam have different pore sizes. Chinese patent with publication number CN113429622A discloses a method for rapidly preparing a double-layer structure foam with low residual monomer content, wherein the pore diameter of the upper open-cell foam is 50 μm to 120 μm, and the pore diameter of the lower open-cell foam material is 1 μm to 30 μm, which are also multi-layer materials with different pore sizes. The national patent with the publication number CN106659816A discloses a high internal phase emulsion foam associated with polyurethane foam, wherein the pores of polyurethane foam are relatively large, and the pores of high internal phase emulsion foam are smaller than those of polyurethane foam, but polyurethane foam has the disadvantages of low absorption rate, easy deformation, which causes deformation of the absorption core composed of open-cell foam material, and poor surface dryness after absorption. At the same time, the common disadvantages of the above-mentioned double-layer porous foam materials are that the two layers of porous materials cause the complexity of the preparation process, and the two layers of materials also cause the overall thickness of the porous material to be thick. If a thinner porous material is to be prepared, the preparation difficulty of the multi-layer porous material will inevitably be greater.
[0007] Therefore, it is hoped to develop a single-layer porous material that can be prepared efficiently, so that the thickness of the porous material is lower, and at the same time the two surfaces of the material have different hydrophilicity and diffusivity, meeting the requirements that the liquid storage and diffusion of the material is mainly on one surface while the other surface remains relatively dry. Summary of the invention
[0008] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing a high internal phase emulsion (HIPE) porous foam material having a hydrophilic gradient in the thickness direction and the application of the high internal phase emulsion foam prepared thereby in sanitary products. The obtained HIPE porous foam material is subjected to different hydrophilic treatment agents on the two surfaces respectively, so that the foam material obtains a hydrophilic gradient in the thickness direction, so that when the liquid contacts the first surface, the diffusion area of the liquid on the first surface is small, the liquid can quickly infiltrate, and the liquid is stored and diffused in the part close to the second surface of the foam material, so that after the liquid is applied at a fixed point on the first surface of the foam material, the diffusion area of the liquid on the second surface is more than 1.5 times the diffusion area of the first surface.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in a thickness direction, the method comprising:
[0011] S1. Preparation of HIPE emulsion
[0012] (a) preparing a water phase, an oil phase, an initiator phase, and an initiator enhancer phase;
[0013] (b) mixing the oil phase and the water phase and emulsifying to obtain a primary HIPE emulsion;
[0014] (c) mixing the initial HIPE emulsion with an initiator phase in proportion, or mixing the initial HIPE emulsion with an initiator phase and an initiator enhancer phase in proportion, and emulsifying to form a curable HIPE emulsion;
[0015] S2, emulsion curing
[0016] The curable HIPE emulsion is coated by a coating device to obtain a continuous HIPE emulsion film, and the continuous HIPE emulsion film is cured by free radical polymerization to obtain a water-containing wet foam sheet;
[0017] S3, squeeze water and dry
[0018] Repeating squeezing and drying the wet foam sheet to reduce the water content of the foam to less than 10%, thereby obtaining a HIPE foam sheet;
[0019] S4. Post-treatment and drying
[0020] The dried HIPE foam sheet is subjected to a hydrophilic post-treatment on both sides, and then dried to remove excess water, thereby obtaining a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction.
[0021] Furthermore, in step S1, the volume ratio of the oil phase to the water phase is 1:10 to 1:100; the initiator phase is added at a volume ratio of 1:0.5 to 1:10 between the oil phase and the initiator phase; and the initiator enhancer phase is added at a volume ratio of 1:0.5 to 1:10 between the oil phase and the initiator enhancer phase;
[0022] Based on 100% of the mass of the oil phase, the oil phase comprises 50-97wt% of a monomer that can be polymerized into a solid foam material, 2-50wt% of a cross-linking agent, 1-40wt% of an emulsifier, and 0-10wt% of other additional components;
[0023] The monomer comprises at least one monofunctional alkyl acrylate or alkyl methacrylate which is insoluble or slightly soluble in water; the crosslinking agent is one of the crosslinkable compounds containing multiple vinyl functional groups;
[0024] Based on 100% of the mass of the emulsifier, the emulsifier includes 30-100wt% of a primary emulsifier and 0-70wt% of a co-emulsifier;
[0025] The additional components include at least one of an oil-soluble initiator, an antioxidant, a plasticizer, a flame retardant, and an antibacterial agent.
[0026] Further, the monomer includes at least one of C2-C18 alkyl acrylate and C2-C18 alkyl methacrylate; the monomer includes at least one of 2-ethylhexyl acrylate, n-butyl acrylate, hexyl acrylate, octyl acrylate, dodecyl acrylate, tetradecyl acrylate, hexadecyl acrylate, octadecyl acrylate, 2-ethylhexyl methacrylate, butyl methacrylate, octyl methacrylate, decyl methacrylate, dodecyl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, and octadecyl methacrylate;
[0027] The crosslinking agent includes at least one of 1,6-hexanediol dimethacrylate, 1,4-butanediol dimethacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dodecyl dimethacrylate, tetradecyl dimethacrylate, divinylbenzene, glucose pentaacrylate, and sorbitan pentaacrylate;
[0028] The main emulsifier includes at least one of sorbitan monofatty acid ester, alkyl glycidyl ether, diglycerol monoester, polyglycerol monoester, alkyl polyglycerol ether, alkyl alcohol amide polyglycerol ether, polyglycerol succinate, and sucrose fatty acid ester; the co-emulsifier includes at least one of di-long-chain alkyl quaternary ammonium salt, di-long-chain ester quaternary ammonium salt, long-chain alkyl betaine, alkyl amide betaine, sulfopropyl betaine, hydroxysulfopropyl betaine, and phosphate betaine.
[0029] Furthermore, the aqueous phase is an aqueous solution of one or more electrolytes, and the electrolyte concentration in the aqueous phase is 1-10wt%; the initiator phase is an aqueous solution of a water-soluble free radical initiator with a concentration of 1-20wt%; the initiator enhancement phase is an aqueous solution of an initiator enhancer with a concentration of 0.1-20wt%.
[0030] Further, the aqueous electrolyte is an aqueous solution of calcium chloride;
[0031] The water-soluble free radical initiator includes one of sodium persulfate, potassium persulfate, ammonium persulfate, azobisisopropylimidazoline hydrochloride, 4,4′-azobis(4-cyanovaleric acid), 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], azobisisobutylimidazoline, azobisisobutylamidine hydrochloride, and azobiscarboxyethyl-2-isobutylamidine hydrate;
[0032] The initiator enhancer is one of sulfite, reducing transition metal inorganic salt and vitamin C.
[0033] Furthermore, the hydrophilic post-treatment method is to apply treatment agent solutions of different hydrophilicities to the two surfaces of the formed HIPE foam sheet respectively; the HIPE foam sheet includes a first surface and a second surface, the hydrophilic treatment agent on the first surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.05% to 15%; the hydrophilic treatment agent on the second surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.2% to 35%; the contact angle between the first surface of the hydrophilically treated HIPE foam sheet and water is always greater than the contact angle between the second surface of the hydrophilically treated HIPE foam sheet and water.
[0034] Furthermore, the hydrophilic post-treatment of the HIPE foam sheet is performed by applying an aqueous solution of a hydrophilic treatment agent to two surfaces of the HIPE foam by spraying, rolling or scraping.
[0035] Furthermore, the hydrophilic treatment agent for the first surface of the HIPE foam sheet is an aqueous solution of at least one of polyethylene glycol monolaurate, polyethylene glycol disolaurate, and diisooctyl butenedioate; the hydrophilic treatment agent for the second surface of the HIPE foam is an aqueous solution of at least one of diisooctyl succinate sulfonate, sodium fatty acid methyl ester sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, and sodium linear alkylbenzene sulfonate.
[0036] Furthermore, the contact angle between the first surface of the hydrophilic HIPE foam sheet and water is 60° to 150°; the contact angle between the second surface of the hydrophilic HIPE foam sheet and deionized water is 3° to 120°.
[0037] The invention discloses an application of a porous material having a hydrophilicity gradient in a thickness direction. The porous material having a hydrophilicity gradient in a thickness direction is used as an absorbent core in disposable sanitary products.
[0038] The beneficial effects of the present invention are:
[0039] By applying different hydrophilic treatment agents to the two surfaces of the single-layer HIPE porous foam material, the first surface has lower hydrophilicity and diffusivity, and the second surface has higher hydrophilicity, so that the first surface of the porous material can remain relatively dry after absorbing liquid, and the liquid will diffuse to the second surface of the porous material as soon as possible after absorption, and the storage and diffusion of the liquid on the second surface are better than those on the first surface of the porous material. This not only meets the requirements of low material thickness, simple and efficient process, but also meets the requirements that the liquid storage and diffusion of the material are mainly on the second surface while the first surface remains relatively dry. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope image of the porous material prepared in Example 1a magnified 200 times;
[0041] Figure 2 This is a scanning electron microscope image of the porous material prepared in Example 1a at a magnification of 500 times. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The overall implementation plan is:
[0044] (I) Characteristics and preparation of each component forming HIPE high internal phase emulsion
[0045] 1. Oil phase
[0046] Add monomers, crosslinking agents, emulsifiers in proportion, add or not add additional components, mix well, and obtain an oil phase. Based on 100% of the mass of the oil phase, the oil phase contains 50-97wt% of monomers that can be polymerized into solid foam materials, 2-50wt% of crosslinking agents, 1-40wt% of emulsifiers, and 0-10wt% of other additional components.
[0047] The proportion of the monomer to the oil phase is 20% to 97% by weight, and the preferred proportion is 40% to 80%. The monomer contains at least one monofunctional alkyl acrylate or alkyl methacrylate that is insoluble in water or slightly soluble in water. Examples of such monomers include C2-C18 alkyl acrylates and C2-C18 alkyl methacrylates. Preferred monomers of this type are at least one of 2-ethylhexyl acrylate, n-butyl acrylate, hexyl acrylate, octyl acrylate, dodecyl acrylate, tetradecyl acrylate, hexadecyl acrylate, octadecyl acrylate, 2-ethylhexyl methacrylate, butyl methacrylate, octyl methacrylate, decyl methacrylate, dodecyl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, and octadecyl methacrylate.
[0048] The proportion of the crosslinking agent to the oil phase is 2% to 50% by weight, preferably 10% to 40%. The crosslinking agent is a crosslinkable compound containing multiple vinyl functional groups, and examples of such crosslinking agents include at least one of 1,6-hexanediol dimethacrylate, 1,4-butanediol dimethacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dodecyl dimethacrylate, tetradecyl dimethacrylate, divinylbenzene, glucose pentaacrylate, and sorbitan pentaacrylate.
[0049] The proportion of the emulsifier in the oil phase is 1% to 40% by weight, and the preferred proportion is 3% to 30%. The emulsifier is usually at least partially included in the oil phase. Based on 100% of the mass of the emulsifier, the emulsifier includes 30 to 100wt% of the main emulsifier and 0-70wt% of the co-emulsifier. The preferred main emulsifier includes at least one of sorbitan mono-fatty acid ester, alkyl glycidyl ether, diglycerol monoester, polyglycerol monoester, alkyl polyglycerol ether, alkyl alcohol amide polyglycerol ether, polyglycerol succinate, and sucrose fatty acid ester. The preferred co-emulsifier includes at least one of di-long chain alkyl quaternary ammonium salt, di-long chain ester quaternary ammonium salt, long chain alkyl betaine, alkyl amide betaine, sulfopropyl betaine, hydroxysulfopropyl betaine, and phosphate betaine.
[0050] The oil phase may also contain 0-10wt% of additional components, including at least one of oil-soluble photoinitiator, antioxidant, flame retardant, antibacterial agent and antimicrobial agent; the oil-soluble initiator includes at least one of aryl alkyl ketone compounds, benzophenone compounds and heterocyclic aromatic ketone compounds; the antioxidant includes at least one of hindered phenol antioxidant, hindered ammonia antioxidant, phosphite antioxidant and reducing hydroxy sulfonate; the flame retardant includes at least one of alkyl phosphate, aliphatic halogenated hydrocarbon, phosphate aromatic ester and dicyclopentadiene compounds; the antibacterial agent and antimicrobial agent include at least one of nano zinc oxide, copper oxide, anionic antimicrobial agent, vanillin or ethyl vanillin and quaternary ammonium salt. The additional components are specifically selected according to the need to achieve a specific purpose or addition.
[0051] 2. Water phase
[0052] The aqueous phase of the HIPE emulsion is usually an aqueous solution of one or more electrolytes; it is prepared by dissolving a water-soluble electrolyte in water. The main purpose of the electrolyte in the aqueous phase is to minimize the tendency of the monomers and crosslinking agents in the oil phase to dissolve in the aqueous phase. The proportion of such electrolytes in the aqueous phase is 1% to 10% by mass. A preferred aqueous electrolyte solution is an aqueous calcium chloride solution.
[0053] 3. Initiator phase
[0054] The initiator phase is an aqueous solution of a water-soluble free radical initiator with a concentration of 1 to 20 wt %; the water-soluble free radical initiator is dissolved in water. Suitable initiators include at least one of sodium persulfate, potassium persulfate, ammonium persulfate, azobisisopropylimidazoline hydrochloride, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], azobisisobutylimidazoline, azobisisobutylamidine hydrochloride, and azobiscarboxyethyl-2-isobutylamidine hydrate.
[0055] 4. Optional initiator enhancer phase
[0056] In addition, another optional phase for forming the high internal phase emulsion is an initiator enhancer phase, which is an aqueous solution of an initiator enhancer with a concentration of 0.1 to 20 wt%; the initiator enhancer is prepared by dissolving the initiator enhancer in water. The initiator enhancer includes at least one of sulfite, a reducing transition metal inorganic salt, and vitamin C. The initiator enhancer phase can significantly increase the curing speed of the formed high internal phase emulsion, but also significantly shortens the storage time of the high internal phase emulsion in a pipeline, other flow-conducting fluid or storage tank from formation to curing.
[0057] (II) Process for preparing HIPE foam material
[0058] 1. Preparation of curable HIPE emulsion
[0059] The oil phase and the water phase are mixed and emulsified to obtain the primary HIPE emulsion; then the initiator phase is added, and the initiator enhancer phase is added or not added, and mixed evenly to obtain the curable HIPE emulsion. The volume ratio of the oil phase to the water phase is 1:10 to 1:100; the initiator phase is added at a ratio of 1:0.5 to 1:10 in volume ratio of the oil phase to the initiator phase; the initiator enhancer phase is added at a ratio of 1:0.5 to 1:10 in volume ratio of the oil phase to the initiator phase; and the initiator enhancer phase is added at a ratio of 1:0.5 to 1:10 in volume ratio of the oil phase to the initiator enhancer phase.
[0060] The formation process of the primary HIPE emulsion includes at least one stage of emulsification, and the emulsification process may include multiple ones.
[0061] One method of preparing the primary HIPE emulsion is to use at least one emulsifying kettle for emulsification. When preparing the primary HIPE emulsion by primary emulsification, the oil phase and the water phase are all added to the same emulsifying kettle for emulsification. When preparing the primary HIPE emulsion by at least two-stage emulsification, two methods are used for emulsification; the first method is: at least two emulsification kettles are connected in series to form a multi-stage emulsification device, and the water phase is divided into multiple portions according to the number of emulsification kettles in series (the water phase does not need to be equally divided), and multi-stage emulsification is performed, wherein the first-stage emulsification is to add all the oil phase and a portion of the water phase to the first-stage emulsification kettle for emulsification, and the second-stage emulsification or above is to add a portion of the water phase and all the emulsions formed by the previous stage emulsification to the emulsification kettle of the emulsification stage for emulsification (that is, the oil phase and the first portion of the water phase are emulsified in the first-stage emulsification kettle, and the obtained emulsion is input into the second-stage emulsification kettle for emulsification with the second portion of the water phase, and then the second-stage emulsification method is followed step by step); the second method is: at least two emulsification kettles are connected in parallel to form a first-stage emulsification mechanism, and the first-stage emulsification mechanism is connected in series with at least one emulsification kettle. A multi-stage emulsification device is formed, the oil phase is divided into multiple portions according to the number of parallel emulsification kettles (the oil phase does not need to be equally divided), and the water phase is divided into multiple portions according to the formula a+ab (wherein a is the number of parallel emulsification kettles in the first-stage emulsification mechanism, and b is the number of second-stage and subsequent stages of serial emulsification kettles) (the water phase does not need to be equally divided), one portion of the oil phase and one portion of the water phase are added to each emulsification kettle of the first-stage emulsification mechanism, and each portion of the first-stage emulsification is emulsified by each emulsification kettle of the first-stage emulsification mechanism to form each portion of the first-stage emulsion, and then each portion of the first-stage emulsion is emulsified at the second or higher level. During the emulsification process, when the previous portion of the first-stage emulsion is emulsified at the second or higher level, another emulsification kettle of the first-stage emulsification mechanism emulsifies another portion of the first-stage emulsion, and the second or higher level emulsification is emulsified by adding one portion of the water phase and all the emulsions formed by the previous stage emulsification to the emulsification kettle of the emulsification stage.An optional secondary emulsification method is: three emulsification kettles are connected in parallel to form a first-stage emulsification mechanism, and then the first-stage emulsification mechanism is connected in series with two emulsification kettles to form a multi-stage emulsification device, the oil phase is divided into three parts, and the water phase is divided into nine parts, one part of the oil phase and one part of the water phase are added to the three emulsification kettles of the first-stage emulsification mechanism, and emulsification is performed by the first emulsification kettle of the first-stage emulsification mechanism to form a first part of the first-stage emulsified liquid, the first-stage emulsified liquid is input into the second-stage emulsification kettle and one part of the water phase is added to perform the second-stage emulsification, and the obtained second-stage emulsified liquid is input into the second-stage emulsification kettle and one part of the water phase is added to perform the tertiary emulsification At the same time, when the first portion of the first-stage emulsion is subjected to secondary or tertiary emulsification, it is emulsified by the second emulsifying kettle of the first-stage emulsification mechanism to form a second portion of the first-stage emulsion, and the second portion of the first-stage emulsion is subsequently emulsified in the manner of the secondary or tertiary emulsification of the first portion of the first-stage emulsion. When the second portion of the first-stage emulsion is subjected to secondary or tertiary emulsification, it is emulsified by the third emulsifying kettle of the first-stage emulsification mechanism to form a third portion of the first-stage emulsion, and then secondary or tertiary emulsification is performed in the manner of the secondary or tertiary emulsification of the first portion of the first-stage emulsion.
[0062] Furthermore, in the above method of preparing the primary HIPE emulsion by emulsification using at least one emulsifying kettle, each emulsifying kettle is provided with a reflux pipeline from the outlet of the emulsifying kettle to the emulsifying kettle, and the function of the reflux pipeline is to reflux the incompletely emulsified water phase and oil phase for re-emulsification; any portion of the water phase needs to be heated to between 30°C and 80°C before being added to the emulsifying kettle. When preparing the primary HIPE emulsion by at least two-stage emulsification, an emulsion buffer tank is connected to each stage of the emulsifying kettle, and the emulsion of the previous stage is pumped into the emulsion buffer tank for temporary storage after the emulsification is completed. The liquid buffer tank is provided with a jacket, and the jacket temperature is set to between 30°C and 80°C.
[0063] Another method for preparing the initial HIPE emulsion is to use a dynamic mixer or a homogenizing emulsifying pump for continuous emulsification. The process flow of this continuous emulsification method is simpler and more controllable, the equipment investment and floor space are less, and it is convenient for automated operation and equipment maintenance. The preferred emulsification method is to use a dynamic mixer or a homogenizing emulsifying pump for continuous emulsification to continuously prepare the HIPE emulsion. In this preferred continuous emulsification method, the oil phase and the water phase enter the dynamic mixer or homogenizing emulsifier in proportion through a metering pump, and the metering pump includes but is not limited to common metering pumps such as a rotor metering pump, a diaphragm metering pump, and a plunger pump; the dynamic mixer or emulsifying pump used for emulsification can be single or multiple, and the volume ratio of the oil phase to the water phase through all the homogenizing emulsifying pumps is between 1:10 and 1:100. The emulsification mechanism of the dynamic mixer or homogenizing emulsifying pump comes from the strong emulsification effect brought about by the high tangential speed and high-frequency mechanical effect generated by the high-speed rotation of the rotor. The oil phase and the water phase form the initial HIPE emulsion after being subjected to strong shear force. The static mixer is a single static mixer or multiple static mixers connected in series or in parallel. The preferred static mixer type is an SK type static mixer, or an SX type static mixer, or an SV type static mixer, or an SL type static mixer.
[0064] The primary HIPE emulsion and the initiator phase prepared by the above method are respectively fed into a static mixer through metering pumps, or the primary HIPE emulsion and the initiator phase and the initiator enhancer phase are respectively fed into a static mixer through metering pumps, and are uniformly mixed to form a curable HIPE.
[0065] 2. Emulsion curing
[0066] The curable HIPE emulsion is coated by a coating device to form a continuous HIPE emulsion film; the HIPE emulsion film is cured by free radical polymerization to obtain a water-containing wet foam sheet.
[0067] Curable HIPE emulsions are usually caused by the decomposition of free radical thermal initiators by high temperature to generate free radicals, which initiate free radical polymerization of monomers and crosslinking agents in the oil phase to form polymers, thereby achieving the purpose of curing the HIPE emulsion. In addition, the initiation method of free radical polymerization can also be to add a photoinitiator as an additional component to the oil phase, and generate free radicals by means of light in the HIPE emulsion curing stage to initiate free radical polymerization. In addition, the initiation method of free radical polymerization can also be to add an initiator enhancement phase after the HIPE emulsion is formed, and the reducing components in the initiator enhancement phase undergo a redox reaction with the peroxide or persulfide in the water phase to generate free radicals, thereby initiating free radical polymerization. The emulsion curing method can adopt a variety of well-known free radical polymerization methods and is not limited to the above examples.
[0068] 3. Squeeze water and dry
[0069] The solidified wet foam sheet contains a lot of water in the wet foam. The method for dehydrating the wet foam is to repeatedly squeeze and dry the wet foam to reduce the water content of the foam to less than 10wt%, thereby obtaining a HIPE foam sheet.
[0070] The purpose of squeezing water is to squeeze out the water in the wet foam and reduce the water content in the foam material. Drying can be done by common drying equipment, such as chain plate dryer, vacuum dryer, microwave dryer, etc. The drying temperature is within 130℃; the drying method is blast drying or vacuum drying within 100℃.
[0071] 4. Gradient hydrophilic post-treatment and drying
[0072] This step is the main feature of the present invention. The post-treatment method is to apply a double-sided hydrophilic post-treatment to the HIPE foam sheet (i.e., different hydrophilic treatment agent solutions are applied to the upper and lower surfaces of the formed HIPE foam sheet respectively), and then dry to remove excess water to obtain a porous material with a hydrophilic gradient in the thickness direction. In order to make the single-layer porous material have sufficient liquid storage capacity, the average pore size of the porous material is between 20μm and 80μm.
[0073] In this step, as the hydrophilic treatment agent solution penetrates from the two surfaces to the middle of the HIPE foam, the HIPE foam has a hydrophilic gradient in the thickness direction. The hydrophilic post-treatment method of the two surfaces of the HIPE foam sheet is that the hydrophilic treatment agent aqueous solution is applied to the two surfaces of the HIPE foam sheet by spraying, rolling or scraping. The HIPE foam sheet includes a first surface and a second surface relative to each other, and the contact angle between the first surface of the hydrophilic treated HIPE foam sheet and water is always greater than the contact angle between the second surface of the hydrophilic treated HIPE foam sheet and water. The contact angle between the first surface of the hydrophilic treated HIPE foam sheet and water is 60° to 150°; in a preferred embodiment, the contact angle between the first surface and deionized water is 80° to 140°. The contact angle between the second surface of the hydrophilic treated HIPE foam sheet and deionized water is 3° to 120°, and in a preferred embodiment, the contact angle between the second surface and deionized water is 10° to 90°.
[0074] The hydrophilic treatment agent on the first surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.05% to 15%.
[0075] The hydrophilic treatment agent on the first surface of the HIPE foam sheet is polyethylene glycol monolaurate (chemical formula is HO(CH2CH2O) n OC(CH2) 10 CH3, n is an integer of 1-14), polyethylene glycol dilaurate (chemical formula is CH3(CH2) 10 COO(CH2CH2O)m OC(CH2) 10 CH3, m is an integer of 1-14), an aqueous solution of at least one component of di-2-ethylhexyl butene dioate.
[0076] Preferably, the effective ingredients of the hydrophilic treatment agent for the first surface of the HIPE foam sheet include at least 40 wt % of polyethylene glycol monolaurate and polyethylene glycol dilaurate.
[0077] In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least three polyethylene glycol monolaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least five polyethylene glycol monolaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least seven polyethylene glycol monolaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 10 polyethylene glycol monolaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 12 polyethylene glycol monolaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 14 polyethylene glycol monolaurates with different polymerization degrees.
[0078] In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least three polyethylene glycol dilaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least five polyethylene glycol dilaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least seven polyethylene glycol dilaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 10 polyethylene glycol dilaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 12 polyethylene glycol dilaurates with different polymerization degrees. In a preferred embodiment, the hydrophilic treatment agent on the first surface of the HIPE foam sheet comprises at least 14 polyethylene glycol dilaurates with different polymerization degrees.
[0079] The hydrophilic treatment agent on the second surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.2% to 35%.
[0080] The hydrophilic treatment agent for the second surface of the HIPE foam sheet is an aqueous solution of at least one of diisooctyl succinate sulfonate, sodium fatty acid methyl ester sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, and sodium linear alkylbenzene sulfonate. In a preferred embodiment, diisooctyl succinate sulfonate accounts for at least 40% by weight of the effective components of the hydrophilic treatment agent for the second surface of the HIPE foam.
[0081] The artificial blood infiltration rate of the prepared porous material with a hydrophilic gradient in the thickness direction is within 40 seconds; in a preferred embodiment, the artificial blood infiltration rate is within 30 seconds. After the porous material with a hydrophilic gradient in the thickness direction absorbs 5 to 15 mL of artificial blood from the first surface for 30 minutes, the liquid diffusion area of the second surface of the porous material is at least 1.5 times the liquid diffusion area of the first surface.
[0082] When the porous material with a hydrophilicity gradient in the thickness direction is used in disposable sanitary products, the first surface of the foam material is close to the applicable surface of the disposable sanitary product, which is the side close to the human body during use, and the second surface of the HIPE foam material is close to the impermeable bottom film of the disposable sanitary product, which is the side away from the human body during use.
[0083] (III) Detailed description of test method
[0084] 1. Preparation of artificial blood
[0085] Artificial blood formula:
[0086] Distilled water or deionized water: 860 mL;
[0087] Sodium chloride: 10g;
[0088] Sodium carbonate: 40g;
[0089] Glycerol: 140mL;
[0090] Sodium benzoate: 1g;
[0091] Food coloring: 0.05g;
[0092] Sodium carboxymethyl cellulose: 5g;
[0093] Standard medium: 1% (volume fraction);
[0094] The physical properties of artificial blood should meet the following requirements:
[0095] a) Density: (1.05±0.05) g / cm 3 ;
[0096] b) Viscosity: (11.9±0.7)s (measured with No. 4 paint cup);
[0097] c) Surface tension: (36±4) mN / m
[0098] 2. Absorption rate
[0099] Weigh 0.2±0.01g of HIPE foam material sample, record the weight as m1, put it into a 40mm×60mm tea bag, immerse the empty tea bag and the tea bag with HIPE foam material into artificial blood at the same time, leave for 30 minutes, take out after 30 minutes, hang for 10 minutes to drain, weigh the weight of the empty tea bag m0, weigh the weight of the tea bag with HIPE foam material m2, the absorption ratio C of HIPE foam material is: C=(m2-m0) / m1-1;
[0100] 3. Contact angle
[0101] An optical method based on liquid surface shape analysis is used.
[0102] 4. Absorption rate of artificial blood
[0103] Spread a HIEP foam material with a length of 30 cm and a width of 10 cm on the table, add 5 mL of artificial blood at one time in the middle of the HIPE foam sheet, and the time it takes for the artificial blood to completely penetrate into the HIPE foam material is the absorption rate.
[0104] The specific embodiments are as follows:
[0105] Example 1
[0106] (I) Preparation of HIPE foam sheet from HIPE emulsion
[0107] An oil phase containing 70 wt% isooctyl acrylate, 24 wt% ethylene glycol dimethacrylate, 5 wt% triglycerol monostearate and 1 wt% ditallow dimethyl ammonium methyl sulfate was prepared; a 4 wt% calcium chloride aqueous solution was prepared as the aqueous phase, and the aqueous phase was heated to 65° C.; a 5 wt% sodium persulfate aqueous solution was prepared as the initiator phase. The oil phase passed through a metering pump at a rate of 20 L / hour and entered a three-stage homogenizing emulsification pump, and the aqueous phase passed through another metering pump at a rate of 500 L / hour and entered the same three-stage homogenizing emulsification pump for emulsification (the volume ratio of the oil phase to the aqueous phase was 1:25) to obtain a primary HIPE emulsion. The obtained initial HIPE emulsion is pumped into an emulsion buffer tank (the outlet of the emulsification pump is connected to an emulsion buffer tank with a jacket, the volume of the emulsion buffer tank is 500L, and the temperature in the emulsion buffer tank is controlled at 65°C), and then the initial HIPE emulsion in the emulsion buffer tank is metered by a metering pump and input into an SK type static mixer, and the initiator phase is metered by another metering pump and input into the same static mixer for emulsification to obtain a curable HIPE emulsion, and the volume ratio of the initiator phase to the oil phase is 1:1. The curable HIPE emulsion is coated by a coating device to form a continuous HIPE emulsion film; the HIPE emulsion film is cured by free radical polymerization to obtain a water-containing wet foam sheet; the free radical polymerization curing is carried out in a chain plate type high temperature curing box with a curing section length of 40 meters, the curing temperature is 90°C, and the curing time is 20 minutes. The outlet of the curing box is connected to a water squeezer composed of a 3-row pair of rollers. The solidified wet foam sheet is squeezed by the water squeezer and then enters a chain plate type blast drying box for drying to obtain a dried foam sheet. The chain plate type blast drying box is 40 meters long. The moisture content of the foam after drying in the blast drying box is 7wt%.
[0108] (ii) Preparation of foam material with hydrophilicity gradient in thickness direction
[0109] The two surfaces of the dried HIPE foam sheet are subjected to hydrophilic post-treatment by spraying; after the hydrophilic treatment, the sheet is dried to obtain a porous material with a hydrophilic gradient in the thickness direction within a water content of less than 7wt%, and the average pore size of the porous material is between 20μm and 80μm. The composition and concentration of the hydrophilic treatment agent on the two surfaces are shown in Table 1:
[0110] Table 1
[0111]
[0112] Comparative Example 1
[0113] A HIPE foam sheet was prepared according to the method of Example 1, and then the obtained HIPE foam sheet was immersed in a hydrophilic post-treatment liquid tank containing 1 wt% sorbitan laurate as a hydrophilic treatment agent, and then squeezed and dried after being treated with the hydrophilic treatment liquid to obtain a hydrophilic foam material with a water content of less than 7%.
[0114] The performance comparison of the foam materials prepared in Example 1 and Comparative Example 1 is shown in Table 2:
[0115] Table 2
[0116]
[0117] From the above data, it can be concluded that the method for forming the hydrophilicity gradient in Example 1 enables the foam material to have a bottom diffusion effect, so that the single-layer material has the effect of the double-layer material with different pore sizes and hydrophilicity in the prior art.
[0118] Example 2
[0119] The foam material was prepared according to the method of Example 1, except that the initial HIPE emulsion was prepared by adding the oil phase and the water phase into the same emulsifying kettle for emulsification to obtain the initial HIPE emulsion. The hydrophilic treatment agent on both surfaces of the HIPE foam sheet was the same as that in Example 1d.
[0120] Example 3
[0121] The foam material was prepared according to the method of Example 1, except that the initial HIPE emulsion was prepared by connecting three emulsifying kettles in parallel to form a first-stage emulsifying mechanism, and then connecting the first-stage emulsifying mechanism and two emulsifying kettles in series to form a multi-stage emulsifying device; the oil phase was divided into three equal volumes, and the water phase was divided into nine equal volumes, and one portion of the oil phase and one portion of the water phase were added to each of the three emulsifying kettles of the first-stage emulsifying mechanism, and emulsified by the first emulsifying kettle of the first-stage emulsifying mechanism to form a first portion of the first-stage emulsion, the first-stage emulsion was input into a second-stage emulsifying kettle and one portion of the water phase was added for second-stage emulsification, and the obtained second-stage emulsion was input into a second-stage emulsifying kettle and one portion of the water phase was added to the first emulsifying kettle. The first emulsion is subjected to three-stage emulsification, and when the first emulsion is subjected to two-stage emulsification or three-stage emulsification, the second emulsification kettle of the first emulsification mechanism is used to emulsify the second emulsion, and the second emulsion is subjected to subsequent emulsification in the same manner as the first emulsion, and the third emulsification kettle of the first emulsification mechanism is used to emulsify the third emulsion, and the second emulsion is subjected to two-stage emulsification or three-stage emulsification, and the third emulsification is then carried out in the same manner as the first emulsion, and the first emulsion is subjected to two-stage emulsification or three-stage emulsification to obtain the initial HIPE emulsion. The hydrophilic treatment agent on both surfaces of the HIPE foam sheet is the same as that in Example 1d.
[0122] The properties of the foam materials prepared in Example 2, Example 3 and Example 1d are shown in Table 3:
[0123] Table 3
[0124]
[0125] Example 4
[0126] The foam material was prepared according to the method of Example 1d, except that only 0.7% of polyethylene glycol (9) monolaurate was used as the first surface hydrophilic treatment agent.
[0127] Example 5
[0128] The foam material was prepared according to the method of Example 1d, except that only 0.7% of diisooctyl butenedioate was used as the first surface hydrophilic treatment agent.
[0129] The foam materials prepared in Example 1d and Example 4-5 were subjected to artificial blood absorption tests three times in the same area, and it was found that compared with the first time, the ratio of the lower diffusion area to the upper diffusion area of the foam materials prepared in Example 1d and Example 4-5 in the third time was reduced by 28.7%, 61.2%, and 63%, respectively (the ratio of the lower diffusion area to the upper diffusion area of the foam materials prepared in Examples 4 and 5 in the first time was 1.7 and 1.5, respectively).
[0130] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction, characterized in that: The method includes: S1. Preparation of HIPE emulsion (a) preparing a water phase, an oil phase, an initiator phase, and an initiator enhancer phase; (b) mixing the oil phase and the water phase and emulsifying to obtain a primary HIPE emulsion; (c) mixing the initial HIPE emulsion with an initiator phase in proportion, or mixing the initial HIPE emulsion with an initiator phase and an initiator enhancer phase in proportion, and emulsifying to form a curable HIPE emulsion; S2, emulsion curing The curable HIPE emulsion is coated by a coating device to obtain a continuous HIPE emulsion film, and the continuous HIPE emulsion film is cured by free radical polymerization to obtain a water-containing wet foam sheet; S3, squeeze water and dry Repeating squeezing and drying the wet foam sheet to reduce the water content of the foam to less than 10%, thereby obtaining a HIPE foam sheet; S4. Post-treatment and drying The dried HIPE foam sheet is subjected to a hydrophilic post-treatment on both sides, and then dried to remove excess water, thereby obtaining a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction; The hydrophilic post-treatment method is to apply treatment agent solutions of different hydrophilicities to the two surfaces of the formed HIPE foam sheet respectively; the HIPE foam sheet includes a first surface and a second surface, the hydrophilic treatment agent on the first surface of the HIPE foam sheet is an aqueous solution of polyethylene glycol monolaurate and diisooctyl butenedioate, and the hydrophilic treatment agent on the second surface of the HIPE foam is a sodium fatty acid methyl ester sulfonate solution.
2. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 1, characterized in that: In step S1, the volume ratio of the oil phase to the water phase is 1:10 to 1:100; the initiator phase is added at a volume ratio of 1:0.5 to 1:10 between the oil phase and the initiator phase; the initiator enhancer phase is added at a volume ratio of 1:0.5 to 1:10 between the oil phase and the initiator enhancer phase; Based on 100% of the mass of the oil phase, the oil phase comprises 50-97wt% of a monomer that can be polymerized into a solid foam material, 2-50wt% of a cross-linking agent, 1-40wt% of an emulsifier, and 0-10wt% of other additional components; The monomer comprises at least one monofunctional alkyl acrylate or alkyl methacrylate which is insoluble or slightly soluble in water; the crosslinking agent is one of the crosslinkable compounds containing multiple vinyl functional groups; Based on 100% of the mass of the emulsifier, the emulsifier includes 30-100wt% of the main emulsifier and 0-70wt% of the co-emulsifier; The additional components include at least one of an oil-soluble initiator, an antioxidant, a plasticizer, a flame retardant, and an antibacterial agent.
3. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 2, characterized in that: The monomer includes at least one of 2-ethylhexyl acrylate, n-butyl acrylate, hexyl acrylate, octyl acrylate, dodecyl acrylate, tetradecyl acrylate, hexadecyl acrylate, octadecyl acrylate, 2-ethylhexyl methacrylate, butyl methacrylate, octyl methacrylate, decyl methacrylate, dodecyl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, and octadecyl methacrylate; The crosslinking agent includes at least one of 1,6-hexanediol dimethacrylate, 1,4-butanediol dimethacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dodecyl dimethacrylate, tetradecyl dimethacrylate, divinylbenzene, glucose pentaacrylate, and sorbitan pentaacrylate; The main emulsifier includes at least one of sorbitan monofatty acid ester, alkyl glycidyl ether, diglycerol monoester, polyglycerol monoester, alkyl polyglycerol ether, alkyl alcohol amide polyglycerol ether, polyglycerol succinate, and sucrose fatty acid ester; the co-emulsifier includes at least one of di-long-chain alkyl quaternary ammonium salt, di-long-chain ester quaternary ammonium salt, long-chain alkyl betaine, alkyl amide betaine, sulfopropyl betaine, hydroxysulfopropyl betaine, and phosphate betaine.
4. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 1 or 2, characterized in that: The aqueous phase is an aqueous solution of one or more electrolytes, and the electrolyte concentration in the aqueous phase is 1-10wt%; the initiator phase is an aqueous solution of a water-soluble free radical initiator with a concentration of 1-20wt%; and the initiator enhancement phase is an aqueous solution of an initiator enhancer with a concentration of 0.1-20wt%.
5. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 4, characterized in that: The aqueous electrolyte is a calcium chloride aqueous solution; The water-soluble free radical initiator includes at least one of sodium persulfate, potassium persulfate, ammonium persulfate, azobisisopropylimidazoline hydrochloride, 4,4′-azobis(4-cyanovaleric acid), 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], azobisisobutylimidazoline, azobisisobutylamidine hydrochloride, and azobiscarboxyethyl-2-isobutylamidine hydrate; The initiator enhancer includes at least one of sulfite, reducing transition metal inorganic salt and vitamin C.
6. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 1, characterized in that: The hydrophilic treatment agent on the first surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.05% to 15%; the hydrophilic treatment agent on the second surface of the HIPE foam sheet is an aqueous solution with a concentration of 0.2% to 35%; the contact angle between the first surface of the hydrophilically treated HIPE foam sheet and water is always greater than the contact angle between the second surface of the hydrophilically treated HIPE foam sheet and water.
7. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 1 or 6, characterized in that: The hydrophilic post-treatment method of the HIPE foam sheet is to apply the hydrophilic treatment agent aqueous solution to the two surfaces of the HIPE foam by spraying, rolling or scraping.
8. The method for preparing a high internal phase emulsion porous foam material having a hydrophilicity gradient in the thickness direction according to claim 6, characterized in that: The contact angle between the first surface of the hydrophilic HIPE foam sheet and water is 60° to 150°; the contact angle between the second surface of the hydrophilic HIPE foam sheet and deionized water is 3° to 120°.
9. Use of a porous material having a hydrophilicity gradient in the thickness direction prepared by the method according to any one of claims 1 to 8, characterized in that: The high internal phase emulsion porous material with a hydrophilicity gradient in the thickness direction is used as an absorbent core in disposable sanitary products.
Citation Information
Patent Citations
Absorbent article with dual core
CN103917210A
Absorbent article with dual core
CN105451702A
Absorbent article with dual core
CN106456412A
Open cell foam associated with a second open cell foam
CN106470711A
High internal phase emulsion foam associated with polyurethane foam
CN106659816A